KESENIAN JANENGAN; IDENTITAS KEETNISAN MASYARAKAT JAWA DI PAJARESUK LAMPUNG - Fitrianto Fitrianto (Graduate School of the Indonesia Institute of the Arts Yogyakarta, 2017)
The emigration of nations from Java to Lampung whichtakes placefor many years, precisely since 1905, sets off the occurrence of the social and cultural development that includes adaption and formation of identity. The question of identity is a part of each person’s life either individually or in groups who experience with it a differentiator or a commonality with a human being or another group. One material that can be used in the identification process is art. As it happens in the Javanese society in Pajaresuk, Pringsewu, Lampung which represents the art of Janengan to assert its identity as Javanese. The purpose of this research is to find out what kind of presentation form and play scheme the Janengan art contents, as well as how Janengan art becomes the identity of the Javanese society in Pajaresuk, Pringsewu, Lampung. This research has the quality of descriptive analytical methods andan Etnomusicological perspective. Based on this procedure it can be said that Janengan art describes the identity of Javanese society in Pajaresuk, Pringsewu, Lampung by dint of elements of Javanese culture that contained in it.